Reproduction at the extremes: pseudovivipary, hybridization and genetic mosaicism in Posidonia australis (Posidoniaceae) - Sinclair, E.; Statton, J.; Hovey, R.; Anthony, J.; Dixon, Kingsley; Kendrick, G. (Oxford University Press, 2016)
BACKGROUND AND AIMS: Organisms occupying the edges of natural geographical ranges usually survive at the extreme limits of their innate physiological tolerances. Extreme and prolonged fluctuations in environmental conditions, often associated with climate change and exacerbated at species' geographical range edges, are known to trigger alternative responses in reproduction. This study reports the first observations of adventitious inflorescence-derived plantlet formation in the marine angiosperm Posidonia australis, growing at the northern range edge (upper thermal and salinity tolerance) in Shark Bay, Western Australia. These novel plantlets are described and a combination of microsatellite DNA markers and flow cytometry is used to determine their origin. METHODS: Polymorphic microsatellite DNA markers were used to generate multilocus genotypes to determine the origin of the adventitious inflorescence-derived plantlets. Ploidy and genome size were estimated using flow cytometry. KEY RESULTS: All adventitious plantlets were genetically identical to the maternal plant and were therefore the product of a novel pseudoviviparous reproductive event. It was found that 87?% of the multilocus genotypes contained three alleles in at least one locus. Ploidy was identical in all sampled plants. The genome size (2?C value) for samples from Shark Bay and from a separate site much further south was not significantly different, implying they are the same ploidy level and ruling out a complete genome duplication (polyploidy). CONCLUSIONS: Survival at range edges often sees the development of novel responses in the struggle for survival and reproduction. This study documents a physiological response at the trailing edge, whereby reproductive strategy can adapt to fluctuating conditions and suggests that the lower-than-usual water temperature triggered unfertilized inflorescences to 'switch' to growing plantlets that were adventitious clones of their maternal parent. This may have important long-term implications as both genetic and ecological constraints may limit the ability to adapt or range-shift; this seagrass meadow in Shark Bay already has low genetic diversity, no sexual reproduction and no seedling recruitment.